Organo-Montmorillonite Modified by Gemini Quaternary Ammonium Surfactants with Different Counterions for Adsorption toward Phenol - Ran Wei; Yuanhua Mo; Duojiao Fu; Hongqin Liu; Baocai Xu (Molecules, 2023)
The discharge of industrial phenol pollutants causes great harm to the natural environment and human health. In this study, phenol removal from water was studied via the adsorption of Na–montmorillonite (Na–Mt) modified by a series of Gemini quaternary ammonium surfactants with different counterions [(C11H23CONH(CH2)2N+ (CH3)2(CH2)2 N+(CH3)2 (CH2)2NHCOC11H23·2Y−, Y = CH3CO3−, C6H5COO− and Br−, 12–2–12·2Y−]. The results of the phenol adsorption indicated that MMt–12–2–12·2Br−, MMt–12–2–12·2CH3CO3− and MMt–12–2–12·2C6H5COO− reached the optimum adsorption capacity, which was 115.110 mg/g, 100.834 mg/g and 99.985 mg/g, respectively, under the conditions of the saturated intercalation concentration at 2.0 times that of the cation exchange capacity (CEC) of the original Na–Mt, 0.04 g of adsorbent and a pH = 10. The adsorption kinetics of all adsorption processes were in good agreement with the pseudo-second-order kinetics model, and the adsorption isotherm was better modeled by Freundlich isotherm. Thermodynamic parameters revealed that the adsorption of phenol was a physical, spontaneous and exothermic process. The results also showed that the counterions of the surfactant had a certain influence on the adsorption performance of MMt for phenol, especially the rigid structure, hydrophobicity, and hydration of the counterions.